2011
DOI: 10.1038/aja.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and clinical correlates of sperm DNA damage

Abstract: Among the different DNA anomalies that can be present in the male gamete, DNA fragmentation is the most frequent, particularly in infertile subjects. There is now consistent evidence that a sperm containing fragmented DNA can be alive, motile, morphologically normal and able to fertilize an oocyte. There is also evidence that the oocyte is able to repair DNA damage; however, the extent of this repair depends on the type of DNA damage present in the sperm, as well as on the quality of the oocyte. Thus, it is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 97 publications
0
71
0
2
Order By: Relevance
“…Low and medium concentrations of ROS are involved in cellular defense against infection agents, signal transduction, and response against mitogens, carboxylation, peroxidation, Pasqualotto et al [28] 0.03 ml [33] and reduction of ribonucleotides; however, high levels of ROS lead to various cellular damage [54][55][56][57][58][59]. ROS induced DNA damage involves base modifications, abasic sites, single strand (ss) and double strand (ds) DNA breaks, and DNA protein cross-links [60][61][62].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 99%
“…Low and medium concentrations of ROS are involved in cellular defense against infection agents, signal transduction, and response against mitogens, carboxylation, peroxidation, Pasqualotto et al [28] 0.03 ml [33] and reduction of ribonucleotides; however, high levels of ROS lead to various cellular damage [54][55][56][57][58][59]. ROS induced DNA damage involves base modifications, abasic sites, single strand (ss) and double strand (ds) DNA breaks, and DNA protein cross-links [60][61][62].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 99%
“…4,15,71,72 Recent studies have shown that DNA fragmentation can be primarily attributed to cryopreservation-induced ROS. [73][74][75] In contrast to superoxide anion, the more stable H 2 O 2 readily crosses the plasma membrane and is responsible for DNA oxidative damage. 76 Because DNA integrity is essential for achieving fertilisation and enabling embryo development in assisted reproductive technologies, the preservation of DNA during cryostorage is of extreme importance.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…The use of flow cytometry in SCSA makes standardization difficult because of a degree of user-dependent skill and data interpretation. There is a need for standardization of SDF testing and further studies that assess the clinical relevance of SDF (Tamburrino et al, 2012;Drobnis & Johnson, 2015).…”
Section: Introductionmentioning
confidence: 99%